2023
DOI: 10.1002/mame.202300007
|View full text |Cite
|
Sign up to set email alerts
|

MoS2‐Polyaniline Based Flexible Electrochemical Biosensor: Toward pH Monitoring in Human Sweat

Abstract: Wearable pH sensors for sweat analysis have garnered significant scientific attention for the detection of early signs of many physiological diseases. In this study, a MoS2‐polyaniline (PANI) modified screen‐printed carbon electrode (SPCE) is fabricated and used as a sweat biosensor. The exfoliated MoS2 nanosheets are drop casted over an SPCE and are functionalized by a conducting polymer, polyaniline (PANI) via the electropolymerization technique. The as‐fabricated biosensor exhibits high super‐Nernstian sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 85 publications
0
1
0
1
Order By: Relevance
“…A Pani é conhecida por sua capacidade de mudar a sua cor de acordo com o pH do meio [10], essa alteração de cor está associada à uma conversão reversível da Pani entre suas formas ácida (sal esmeraldina -verde) e básica (base esmeraldina -azul). Essa propriedade tem sido muito explorada na construção de sensores óticos de pH, utilizando tanto a Pani pura quanto seus compósitos com os mais diversos materiais [1,10,[29][30][31][32]. A grande maioria desses sensores tratam do controle da cor, pela mudança do sal esmeraldina para a base esmeraldina, ou seja, tratam de sensores de ambientes básicos.…”
Section: Resultsunclassified
“…A Pani é conhecida por sua capacidade de mudar a sua cor de acordo com o pH do meio [10], essa alteração de cor está associada à uma conversão reversível da Pani entre suas formas ácida (sal esmeraldina -verde) e básica (base esmeraldina -azul). Essa propriedade tem sido muito explorada na construção de sensores óticos de pH, utilizando tanto a Pani pura quanto seus compósitos com os mais diversos materiais [1,10,[29][30][31][32]. A grande maioria desses sensores tratam do controle da cor, pela mudança do sal esmeraldina para a base esmeraldina, ou seja, tratam de sensores de ambientes básicos.…”
Section: Resultsunclassified
“…131 One of their most frequent applications is for pH sensing. 132–135 For instance, Monsalve et al demonstrated a pH sensor based on screen printed carbon electrodes functionalized with inkjet printed PANI for sweat analysis. The sensor exhibited a sensitivity of 69.1 mV pH −1 that fits with the Nernst equation.…”
Section: Formulas Of Printable Inks For Sensing Devicesmentioning
confidence: 99%